Lean Ergonomics—an empirical combination of Management Science and Ergonomics - Stefan Brunner; Klaus Kühnel; Klaus Bengler (Zeitschrift für Arbeitswissenschaft, 2023)
Abstract This paper presents Lean Ergonomics (LE) as an employee- and process-related method in a~practice-oriented way. Stagnations in economic improvements of the processes, combined with known, high stresses of the basic workers on the shopfloor with ambiguous starting points of ergonomic measures hold broad analysis and optimization potential. This can be shown exploratively based on LE. 12~representative work processes at large reactors in the chemical industry form the study area. Each individual work process receives a~Lean Ergonomics data set consisting of time data [standard deviation in min & %], objective ergonomics [EAWS] and subjective ergonomics [Borg, NASA-TLX; both pseudonymized]. Two process-identical production halls are provided, which is why KFzA (short questionnaire for work analysis) is also collected anonymously for additional general analysis of work system design. Consequently resulting in a~diverse data structure of quantifiable person-related methods, objective, process-related loads and economically relevant, likewise process-related KPIs. @In diesem Artikel wird Lean Ergonomics (LE) als mitarbeiter- und prozessbezogene Methode in der Praxis vorgestellt. Stagnationen bei wirtschaftlichen Verbesserungen der Prozesse, verbunden mit bekannter, hoher Belastung der Basisarbeitenden am Shopfloor bei jedoch uneindeutigen Ansatzpunkten ergonomischer Maßnahmen bergen breites Analyse- und Optimierungspotential, das explorativ anhand LE aufgezeigt werden kann. 12~repräsentative Arbeitsprozesse an Großreaktoren bilden den Untersuchungsraum. Jeder einzelne Arbeitsprozess erhält ein Lean Ergonomics Daten Set, das sich aus Zeitdaten [Standardabweichung in min & %], objektiver Ergonomie [EAWS] und subjektiver Beanspruchung [Borg, NASA-TLX; beide pseudonymisiert] zusammensetzt. Es stehen 2~prozessual identische Produktionshallen zur Verfügung. Zur weiteren allgemeineren Analyse des Arbeitssystems wird der Kurzfragebogen zur Arbeitsanalyse (KFzA) pseudonymisiert erhoben. Folglich ergibt sich eine vielfältige Datenstruktur an quantifizierbaren personenbezogenen Methoden, objektiven, prozessbezogenen Belastungsfaktoren und wirtschaftlich relevanten, ebenso prozessbezogenen Key Performance Indicators (KPIs).
Keywords: 330; Lean Ergonomics; Lean Management; Human Factors Engineering; Operational Excellence; Ergonomie